PERAN BINUCA (Bureau Intégré de l'Organisation des Nations Unies en Centrafrique) DALAM MENJAGA PERDAMAIAN - Widianti, Herni; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about how the BINUCA’s roles as international organization to keep peace in Central African Republic (2010-2014). The Rebelion and violent coup made this country fail to protect the security and welfare of civilians even since gaining independence from France in 1960. Central African Republic became weakness of state capacity and authority in many core state function. The worst part is when political conflict turn into ethnic cleansing between Séléka and anti-Balaka.This research used qualitative methods. In this research, the data was collected by using library research technique where this technique is collecting data sources from the literature, like books, website official publications, newspaper, and journal.This research uses pluralism approach which this approach has assumption that actor in international relation isn’t just a state but there’s another actor one of International organization. In this research, writer uses International Organization Theory which each organization has their duty. This research of BINUCA has important duties and roles to keep peace in Central African Republic.To keep peace in Central African Republic, BINUCA has three roles, political, law and security asspects. Those the most important things at that time to be solved.Keywords: BINUCA, Rebelion, Coup, Genocide, Government, Peace